Rosiglitazone induces decreases in bone mass and strength that are reminiscent of aged bone - Lazarenko, Oxana P. (2007)
PPARγ regulates both glucose metabolism and bone mass. Recent evidence suggests that the therapeutic modulation of PPARγ activity with anti-diabetic thiazolidinediones elicits unwanted effects on bone. In this study, the effects of rosiglitazone on the skeleton of growing (1 month), adult (6 month), and aged (24 month) C57BL/6 mice were determined. Aging was identified as a confounding factor for rosiglitazone-induced bone loss that correlated with the increased expression of PPARγ in bone marrow mesenchymal stem cells. The bone of young growing mice was least affected, although a significant decrease in bone formation rate was noted. In both adult and aged animals bone volume was significantly decreased by rosiglitazone. In adult animals bone loss correlated with attenuated bone formation, whereas in aged animals bone loss was associated with increased osteoclastogenesis, mediated by increased RANKL expression. PPARγ activation led to changes in marrow structure and function such as a decrease in osteoblast number, an increase in marrow fat cells, an increase in osteoclast number, and a loss of the multipotential character of marrow mesenchymal stem cells. In conclusion, rosiglitazone induces changes in bone reminiscent of aged bone and appears to induce bone loss by altering the phenotype of marrow mesenchymal stem cells.